Factors associated with early initiation of breastfeeding in Western Nepal - Khanal, V.; Scott, J.; Lee, Andy; Karkee, R.; Binns, Colin (MDPI AG, 2015)
The initiation of breastfeeding within one hour of birth has numerous nutritional and immunological benefits and has been found to reduce neonatal mortality. This community-based prospective cohort study aimed to report the rate of, and factors associated with, early initiation of breastfeeding in Western Nepal. The rate of early initiation of breastfeeding was reported, and associations between early initiation and independent variables were tested by Chi-square test, followed by multiple logistic regression. Of the 735 mother-infant pairs, a total of 310 (42.2%) reported early initiation. Mothers who were assisted by traditional attendants during childbirth, delivered by caesarean section, from ethnically disadvantaged families and had delivered low birth weight infants, were less likely to initiate breastfeeding early whereas the mothers who were from the poorest families and did not introduce prelacteal feeds to their infants were more likely to initiate breastfeeding within the first hour. Skills-training to support breastfeeding as part of the training of skilled birth attendants and other health workers is likely to promote recommended infant feeding practices.